2010
DOI: 10.31729/jnma.97
|View full text |Cite
|
Sign up to set email alerts
|

Self Injurious Behavior in Temporal Lobe Epilepsy

Abstract: Self-injurious behavior (SIB) or self-mutilating behavior (SMB) is rare but can occur in temporal lobe epilepsy. Such a behavior during seizures is not usually recalled by patient. Here is a case with self mutilating behavior in left temporal lobe epilepsy, presented because of its rare manifestation and diagnostic dilemma. A 19 year old unmarried Muslim student presented to emergency with SMB, guilty rumination and a persecutory delusion. The patient was intermittently confused about place and time. In subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…5 A Nepalese study among seizure cases referred to a psychiatric service showed 45% with ICD-10 mental and behavioral disorder and the rest at least with some clinically significant symptom in Brief Psychiatric Rating Scale. 10 Depression, mania, 9 anxiety and other neurotic (including dissociation conversion), psychotic disorders, personality and cognitive changes, suicide and self injurious behaviors 8 were seen in these cases as reported elsewhere. 11 This increases the chance of pseudo-seizure in seizure disorders.…”
Section: Discussionsupporting
confidence: 69%
“…5 A Nepalese study among seizure cases referred to a psychiatric service showed 45% with ICD-10 mental and behavioral disorder and the rest at least with some clinically significant symptom in Brief Psychiatric Rating Scale. 10 Depression, mania, 9 anxiety and other neurotic (including dissociation conversion), psychotic disorders, personality and cognitive changes, suicide and self injurious behaviors 8 were seen in these cases as reported elsewhere. 11 This increases the chance of pseudo-seizure in seizure disorders.…”
Section: Discussionsupporting
confidence: 69%
“…Sleep disturbances are also increased in individuals with SIB, but the nature of the association is unclear (Brylewski and Wiggs 1999;de Winter et al 2011;Quine 1991). Epilepsy is another medical condition that may have a role in SIB, as patients with temporal lobe seizures can have associated irritability or aggression, and several case studies have reported improved SIB after treatment of seizures (Bear et al 1982;Blumer 2000;Davanzo and King 1996;Shakya et al 2010). Several recent studies have found no increased prevalence of aggression between groups with and without epilepsy (de Winter et al 2011;Matson et al 1999;Matthews et al 2008).…”
Section: Gamma-aminobutyric Acid Systemmentioning
confidence: 93%
“…They reported a 19-year-old male who presented to emergency with self-injury, guilty rumination, and delusion of persecution and was treated with antiepileptic and antipsychotic medications. [ 14 ] Hence, prompt diagnosis and treatment of SIB in epilepsy patients should be done so that a holistic management is undertaken leading to better functioning and quality of life.…”
Section: Discussionmentioning
confidence: 99%